THE RESILIENCE OF ADOLESCENTS IN THE AREA OF EX LOCALIZATION OF BANDUNG - Any Andriani; Neti Juniarti; Efri Widianti (Faculty of Nursing, Universitas Jember, 2017)
Localization is a gathering place for commercial sex workers (CSWs) and identical to a negative environment. Localization can influence the development and self-information in adolescents. Resilience becomes an important aspect for the individual in overcoming and improving themselves to face difficulties and challenges that they experienced. This study aimed to determine the resilience of adolescents in the area of ex localization of Bandung. This study used a quantitative descriptive method. The sample was 42 adolescents which were taken using total sampling technique The data collection used 25-Items Scale Resilience instrument. The results showed that resilience level of adolescents at ex localization of Bandung was low in some respondents (54.8%) and some of the other respondents (40.5%) were in moderate level. Very few respondents (4.8%) were in a high level of resilience. The conclusion from this study showed that adolescents at ex localization area of Bandung were in low resilience level. Based on the results, holding positive activities that involved adolescents and conducting further research on the factors that affect adolescents resilience at ex-localization area of Bandung are recommended.